2013
DOI: 10.1159/000348778
|View full text |Cite
|
Sign up to set email alerts
|

Normalisation of Angiogenic Imbalance after Intra-Uterine Transfusion for Mirror Syndrome Caused by Parvovirus B19

Abstract: We report a case of mirror syndrome caused by parvovirus B19, which resolved after intra-uterine transfusion. Mirror syndrome is a rare condition characterised by a triad of foetal hydrops, generalized maternal oedema and placentomegaly. Although the mechanism underlying the onset of this syndrome is unknown, it probably shares a common pathophysiologic origin with pre-eclampsia. Our patient showed increased circulating levels of soluble fms-like tyrosine kinase 1 (sFlt-1) and decreased levels of placental gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
2
16
0
4
Order By: Relevance
“…For example, Llurba et al [28] described an unbalanced anti-angiogenic state in pregnancy complicated by hydrops fetalis. In a different case, low PlGF levels returned to normal values after treatment of fetal hydrops related to parvo B19 infection by intrauterine blood transfusion [29]. Finally, in a comprehensive longitudinal study of pregnancy, where most pregnancy complications were not placenta related, lower than normal PlGF levels were found in cases that eventually resulted in fetal death [18].…”
Section: Discussionmentioning
confidence: 92%
“…For example, Llurba et al [28] described an unbalanced anti-angiogenic state in pregnancy complicated by hydrops fetalis. In a different case, low PlGF levels returned to normal values after treatment of fetal hydrops related to parvo B19 infection by intrauterine blood transfusion [29]. Finally, in a comprehensive longitudinal study of pregnancy, where most pregnancy complications were not placenta related, lower than normal PlGF levels were found in cases that eventually resulted in fetal death [18].…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, some case reports have shown that in the exceptional cases of PE in whom placental function improves and symptoms wear off -paradigmatically in mirror syndrome with fetal hydrops of reversible etiologythe initially elevated sFlt-1/PlGF ratio returns to normal values [36,37]. These dynamic variations according to the clinical situation are not so obvious for other classical features of PE, such as uterine artery Doppler, uric acid, liver enzymes, creatinine, or even blood pressure and proteinuria [16,22,33].…”
Section: Aid In Management and Prognosismentioning
confidence: 99%
“…Additionally, we found remarkable increase in serum hCG level. Elevation of serum hCG is known as a feature of MS [ 5 ]. Considering that hydantidiform mole, another disease characterized by hydropic change of villi, also shows high hCG level in the peripheral blood, hCG might be related to placental damage caused by edematous tissue change.…”
Section: Discussionmentioning
confidence: 99%